New genera and species of the minute snakeflies (Raphidioptera: Mesoraphidiidae: Nanoraphidiini) from the mid Cretaceous of Myanmar - Liu, Xingyue; Lu, Xiumei; Zhang, Weiwei (Zootaxa, 2016)
The Mesozoic amber snakeflies are important for understanding the early evolution and phylogeny of Raphidioptera. Here we describe three new genera and four new species of the extinct family Mesoraphidiidae from the mid Cretaceous amber of northern Myanmar, including Dolichoraphidia aspoecki gen. et sp. nov., Dolichoraphidia engeli gen. et sp. nov., Rhynchoraphidia burmana gen. et sp. nov., and Burmoraphidia reni gen. et sp. nov. All these species, together with the previously described species (i.e., Nanoraphidia electroburmica Engel, 2002) from Burmese amber, belong to the mesoraphidiid tribe Nanoraphidiini based on the minute body-size and the swollen tibiae. A key to all species of Nanoraphidiini is provided. A brief discussion on the genital morphology of Mesoraphidiidae is also given.